Prevalence and determinants of allergic rhinitis among high school students exposed to industry allergens in Eastern Ethiopia - Selamawit Gashaw; Ayantu Kebede; Gada Edea; Birhanu Yadecha; Moges Tesfaye; Hailu Merga (PLoS ONE, 2025)
Introduction Allergic rhinitis (AR), a common chronic disease triggered by allergens, often leads to school absenteeism in students. Investigating its magnitude and risk factors may play an important role in preventing the disease. Hence, this study aimed to assess the prevalence of allergic rhinitis and associated factors among high school students living in industrial areas in Eastern Ethiopia. Methods A school-based cross-sectional study design was conducted in September 2023 among 442 randomly selected high school students. Data was collected using a structured self-administered questionnaire. Questions on allergic disease symptoms were based on the International Study of Asthma and Allergies in Children (ISAAC) core allergy and environmental questionnaire. Binary logistic regression analysis was done to identify the factors associated with allergic rhinitis. Finally, Adjusted Odds Ratio (AOR), 95% Confidence interval and P-value less than 0.05 was used to judge the statistical significance. Results This study found that the magnitude of allergic rhinitis was 20.7% (95% CI: 17.0%, 24.8%). Similarly, this study identified that a family history of allergic rhinitis (AOR: 2.99, 95% CI: 1.42–6.29) and living with a smoker in the household (AOR: 3.63, 95% CI: 1.22–10.78) were significant risk factors. Conversely, living in a house far from traffic roads (AOR: 0.32, 95% CI: 0.15–0.67) and far from factories (AOR: 0.10, 95% CI: 0.03–0.31) were protective factors against allergic rhinitis. Conclusions The current study found a lower magnitude of allergic rhinitis compared to the previous studies conducted in African countries. Having a smoker family member, distance between the house and nearest traffic road, distance between the house and nearest factory, and family history of allergy rhinitis were factors associated with allergy rhinitis. Hence, provision of health education to encourage people to stop smoking is strongly recommended. Similarly, persons with a family history of allergic rhinitis should minimize exposure to polluted environment and other trigger factors.